Multicast Resource Allocation with Opportunistic Scheduling in LTE Networks - Algharem, Mohammed; Omar, Mohammed Hasbullah; Aldmour, Ismat; Budiarto, Rahmat (Elektronika ir Elektrotechnika, 2018)
Long Term Evolution (LTE) and beyond networks offer high bitrates with low latencies which makes them the best choice to handle the growing demand on multicast mobile services such as video streaming, and news broadcasting. In Conventional Multicast Scheme (CMS), the gain of multicast is exploited by transmitting data to all users simultaneously using the rate of Worst Channel Gain (WCG), which wastes network resources. In this paper, to better balance the tradeoff between the multicast gain and multiuser diversity, we propose a mechanism to select a threshold to split users into two subgroups and exploits the Opportunistic Multicast Scheme (OMS) to transmit the data. Simulation results show that the proposed mechanism improves the multicast performance in terms of increased throughput, decreased delay and Packet Loss Ratio (PLR) compared to existing mechanisms from the literature. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21850